2019
DOI: 10.4254/wjh.v11.i6.489
|View full text |Cite
|
Sign up to set email alerts
|

Dietary approach and gut microbiota modulation for chronic hepatic encephalopathy in cirrhosis

Abstract: Hepatic encephalopathy (HE) is a common and serious neuropsychiatric complication of cirrhosis, acute liver failure, and porto-systemic shunting. HE largely contributes to the morbidity of patients with liver disease, severely affecting the quality of life of both patients and their relatives and being associated with poor prognosis. Its presentation is largely variable, manifesting with a broad spectrum of cognitive abnormalities ranging from subtle cognitive impairment to coma. The pathogenesis of HE is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 225 publications
0
31
0
6
Order By: Relevance
“…The increase in the concentration of these toxic metabolites and the inability of the diseased liver to clear these products are considered to be important pathophysiological effects[ 143 ]. Furthermore, inflammation (systemic or local), leaky gut, bacterial translocation, and overgrowth of small intestinal bacteria are also critical to the pathogenesis of HE[ 158 ].…”
Section: Microbiota-gut-live-brain Axis and Cirrhosis And Hementioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the concentration of these toxic metabolites and the inability of the diseased liver to clear these products are considered to be important pathophysiological effects[ 143 ]. Furthermore, inflammation (systemic or local), leaky gut, bacterial translocation, and overgrowth of small intestinal bacteria are also critical to the pathogenesis of HE[ 158 ].…”
Section: Microbiota-gut-live-brain Axis and Cirrhosis And Hementioning
confidence: 99%
“…However, this conclusion has been overturned. Existing studies have shown that normal protein intake is well tolerated by patients with HE[ 158 ]. Interestingly, a clinical trial study showed that a high-protein, high-calorie diet based on casein-vegetable can significantly reduce the blood ammonia level of patients with HE and improve mental status[ 159 ].…”
Section: Microbiota-gut-live-brain Axis and Cirrhosis And Hementioning
confidence: 99%
“…The major role of the gut microbiota in liver disease is also supported by various studies showing that several complications of serious liver disease, such as hepatic encephalopathy are efficiently treated by the modulation of gut microbiome via use of probiotics, prebiotics and antibiotics [ 107 ]. The pathogenesis of cirrhosis and the precise function of gut microbiome are not yet clear, but these findings that improvement in liver cirrhosis-induced animals and patients highlight the importance of modulation of the gut microbiome, suggesting novel approaches for therapeutic strategies for liver fibrosis.…”
Section: Cirrhosis and Gut Microbiomementioning
confidence: 99%
“…As we mentioned above, ammonia is a significant contributor to HE: normally, the ammonia in the gut lumen is transferred into the liver where it is metabolized into urea via urea cycle but when the host undergoes hyperammonemia or liver diseases, it enters the brain and causes aberrantly functioning neurons (Fig.2) (Wijdicks, 2016). It is a representative example of how the gut, liver, and brain are functionally connected and modulations of gut microbiota by supplementing prebiotics (lactulose) and probiotics, administering antibiotics (rifaximin), altering the dietary structure, and FMT are emerging in HE treatment (Amodio et al, 2014;Campion et al, 2019;Weir, 2020). What accords with the theme here is that HE can be triggered by medications.…”
Section: Connecting the Dots: Gut-liver-brain Aixs In Drug Toxicitymentioning
confidence: 99%